2012
DOI: 10.1371/journal.pone.0038766
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Microenvironmental Sensitivity of Body Weight in Rainbow Trout (Oncorhynchus mykiss) Selected for Improved Growth

Abstract: Microenvironmental sensitivity of a genotype refers to the ability to buffer against non-specific environmental factors, and it can be quantified by the amount of residual variation in a trait expressed by the genotype’s offspring within a (macro)environment. Due to the high degree of polymorphism in behavioral, growth and life-history traits, both farmed and wild salmonids are highly susceptible to microenvironmental variation, yet the heritable basis of this characteristic remains unknown. We estimated the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 79 publications
5
54
6
Order By: Relevance
“…Heritabilities of this magnitude are a marked departure from standard quantitative trait heritabilities, which are typically between 20-60% , and between 30% and 57% for the wing shape traits in this study. Although the average reported heritability of micro-environmental variance in agricultural populations is higher than found here (3.8%: Hill and Mulder 2010), a similarly large difference (an order of magnitude) in heritability between a trait mean and its micro-environmental variance is typical of agricultural studies (e.g., Wolc et al 2009;Mulder et al 2009;Wolc et al 2011;Janhunen et al 2012). …”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Heritabilities of this magnitude are a marked departure from standard quantitative trait heritabilities, which are typically between 20-60% , and between 30% and 57% for the wing shape traits in this study. Although the average reported heritability of micro-environmental variance in agricultural populations is higher than found here (3.8%: Hill and Mulder 2010), a similarly large difference (an order of magnitude) in heritability between a trait mean and its micro-environmental variance is typical of agricultural studies (e.g., Wolc et al 2009;Mulder et al 2009;Wolc et al 2011;Janhunen et al 2012). …”
Section: Discussioncontrasting
confidence: 51%
“…Wolc et al 2009;Mulder et al 2009;Janhunen et al 2012). The first step employed a standard quantitative genetic model to estimate the additive genetic, dominance genetic, and residual variance for the means of the wing-shape traits ( ) and for the mean of fitness (w).…”
Section: General Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A thorough understanding of the genetic control of growth traits in rainbow trout is key to genetic enhancements in production performance. On the basis of animal and plant breeding science, genetic improvement in aquaculture has been successfully implemented during the past three decades, particularly in salmonid farming, and is still in progress (Donaldson, 1969;Gall and Crandell, 1992;Janhunen et al, 2012;Kause et al, 2012;Sae-Lim et al, 2012). Coldwater fish culturing in China began in 1959, when eyed eggs and fry of rainbow trout were introduced from the Democratic People's Republic of Korea.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Atlantic salmon, rainbow trout, and Nile tilapia found a large genetic component in variability of body weight (Janhunen et al, 2012;Sonesson et al, 2013;Sae-Lim, et al, 2015a;Sae-Lim, et al, 2015b;.…”
Section: Social Interactions and Inherited Variabilitymentioning
confidence: 99%